P074 PARASTOMAL AND INCISIONAL HERNIAS FOLLOWING EMERGENCY SURGERY FOR HINCHEY III-IV DIVERTICULITIS: A SYSTEMATIC REVIEW. (25th November 2021) - Mäkäräinen, Elisa; Rautio, Tero; Muysoms, Filip; Kauppila, Joonas
Abstract: Aim: The aim of this systematic review was to report the risk of parastomal and incisional hernias after emergency surgery for Hinchey III–IV diverticulitis. Material and Methods: The Cochrane Library, Embase, PubMed (MEDLINE), Web of Science and Scopus databases were systematically searched. All randomized controlled trials (RCTs) and cohort studies comparing HP with other surgical treatment options for perforated diverticulitis classified as purulent or faecal (Hinchey III–IV) were considered for inclusion. Exclusion criteria were case series and reports, letters, editorials, reviews and conference abstracts. The primary endpoint was parastomal hernia incidence. The secondary endpoint was incisional hernia incidence. Seven studies (six randomized controlled trials and one retrospective cohort) with a total of 831 patients were eligible for inclusion. Results: The parastomal hernia incidence was 15.2–46.0% for Hartmann procedure, 0–85.2% for primary anastomosis, 4.3% for resection and 1.6 % for laparoscopic lavage. The incisional hernia incidences were 7.8–38.1% for Hartmann procedure, 4.5–27.2% for primary anastomosis, 3.2–25.5% for primary resection, 2.7–11.1% for laparoscopic lavage and 16.1–45.8% for secondary resection. Due to heterogeneity of follow-up methods, follow-up time and lack of both parastomal and incisional hernia as outcome, no meta-analysis was conducted. Conclusions: The hernia incidences reported after surgical treatment for complicated diverticulitis may be biased and underestimated. For future RCTs, researchers are encouraged to pay attention to hernia diagnosis, symptoms and prevention.